Evidence-based Psychopharmacological Treatments for Pediatric Bipolar Disorder - Pınar Uran; Elif Akçay (Galenos Publishing House, 2024)
Bipolar disorder is a chronic illness that often onsets in early stages of life, and the first episode of bipolar disorder frequently occurs in adolescence. Pediatric bipolar disorder (PBD) has more severe symptoms and a poorer prognosis compared to bipolar disorder in adults. Due to limited data on the psychopharmacological treatment of PBD, children and adolescents have been treated primarily in consideration of the findings obtained from clinical studies performed in adults. The efficacy of the psychotropic agents seems to differ in children and adolescents compared to adults. The evidence-based psychopharmacological treatment modalities of PBD are of growing interest in children and adolescents. This review discusses current Food and Drug Administration approved medications for PBD and guidelines for PBD. The psychopharmacologic evidence and algorithms of PBD treatment relevant to different stages of bipolar disorder, including acute manic/mixed episodes, bipolar depression, and maintenance treatment are examined in this review article.